2022
DOI: 10.3389/fmicb.2022.823120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IR Biotyper for Lactiplantibacillus plantarum Typing and Its Application Potential in Probiotic Preliminary Screening

Abstract: IR Biotyper (IRBT), which is a spectroscopic system for microorganism typing based on Fourier transform infrared (FTIR) technology, has been used to detect the spread of clones in clinical microbiology laboratories. However, the use of IRBT to detect probiotics has rarely been reported. Herein, we evaluated the discriminatory power of IRBT to type Lactiplantibacillus plantarum isolates at the strain level and explored its application potential in probiotic preliminary selection. Twenty Lactiplantibacillus isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…First, we spotted 12 μL instead of 15 μL of bacterial suspension from all three agar media onto silicon plates to reduce the amount of bacterial suspension. Second, the sample preparation sequence was changed from an EtOH-water method to a water-EtOH method [ 16 , 18 ]. Lastly, the amount of bacteria was reduced from a 1 μL loopful of bacterial culture to 0.5 μL loopful of bacterial culture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we spotted 12 μL instead of 15 μL of bacterial suspension from all three agar media onto silicon plates to reduce the amount of bacterial suspension. Second, the sample preparation sequence was changed from an EtOH-water method to a water-EtOH method [ 16 , 18 ]. Lastly, the amount of bacteria was reduced from a 1 μL loopful of bacterial culture to 0.5 μL loopful of bacterial culture.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, FTIR spectroscopy techniques could be an alternative for rapid and accurate strain typing. To date, Klebsiella pneumoniae , Acinetobacter baumannii , and Lactiplantibacillus plantarum have been evaluated for strain typing using the IRBT ® [ 16 , 18 , 26 ]. However, this method is challenging for S. aureus strain typing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has shown extensive reports illustrating the discriminatory power among both Gram-positive and Gram-negative bacteria, particularly Listeria spp., Bacillus spp., Pseudomonas spp., Klebsiella spp., and Salmonella spp., both at the genus and species levels ( Quintelas et al., 2018 ; Hu et al, 2020 ; Rakovitsky et al, 2020 ; Cordovana et al, 2021 ; Mullie et al, 2022 ; Pascale et al, 2022 ; Wang-Wang et al, 2022 ). The IR Biotyper has proven to be an effective tool for microbial strain typing, specifically for those pathogens that are associated with nosocomial outbreaks within the hospital setting ( Deidda et al, 2021 ; Lombardo et al, 2021 ; Guerro-Lozano et al, 2022 ; Hadas et al, 2022 ; Li et al, 2022 ; Passaris et. al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…lactis , demonstrating to overcome some limitations of genomic-based methodologies and detecting phenotypic information that cannot be evidenced by DNA-based techniques. In addition, another work on discriminating Lactiplantibacillus plantarum strains demonstrated that FTIRS was not only comparable to WGS and PFGE but also had a higher discriminatory power than MLST ( Li et al, 2022 ). This complies with the fact that the identification of bacteria at the strain level, revealing genetic information evidenced by phenotypic characteristics, is becoming increasingly important in modern microbiology.…”
Section: Introductionmentioning
confidence: 99%